1998
DOI: 10.1097/00000374-199802000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monensin on Ethanol-Induced Alterations in Function of Hepatocellular Asialoglycoprotein Receptor Subpopulations

Abstract: Chronic ethanol consumption is associated with multiple impairments in receptor-mediated endocytosis (RME) in hepatocytes. RME mediated by the asialoglycoprotein receptor seems to be especially impaired by ethanol. In the present study, we determined susceptibility of RME to alterations in ethanol-fed and pair-fed control animals by the addition of a carboxylic ionophore, monensin. Monensin inhibits acidification of prelysosomal vesicular compartments, which results in a decrease in the rate of receptor-ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2004
2004

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…We have extensively studied the process of RME by the hepatocyte-specific asialoglycoprotein receptor (ASGP-R) and have identified multiple steps of this pathway that are affected by ethanol treatment (Casey et al, 1987(Casey et al, , 1990Tworek et al, 1996Tworek et al, , 1997Tworek et al, , 1998b. We have extensively studied the process of RME by the hepatocyte-specific asialoglycoprotein receptor (ASGP-R) and have identified multiple steps of this pathway that are affected by ethanol treatment (Casey et al, 1987(Casey et al, , 1990Tworek et al, 1996Tworek et al, , 1997Tworek et al, , 1998b.…”
Section: Carol a Caseymentioning
confidence: 99%
“…We have extensively studied the process of RME by the hepatocyte-specific asialoglycoprotein receptor (ASGP-R) and have identified multiple steps of this pathway that are affected by ethanol treatment (Casey et al, 1987(Casey et al, , 1990Tworek et al, 1996Tworek et al, , 1997Tworek et al, , 1998b. We have extensively studied the process of RME by the hepatocyte-specific asialoglycoprotein receptor (ASGP-R) and have identified multiple steps of this pathway that are affected by ethanol treatment (Casey et al, 1987(Casey et al, , 1990Tworek et al, 1996Tworek et al, , 1997Tworek et al, , 1998b.…”
Section: Carol a Caseymentioning
confidence: 99%
“…Our previous investigations, utilizing the same ethanol‐feeding model used in the current study, have shown that ethanol impairs RME by ASGP‐R. The ethanol‐induced impairments in RME, which include ligand binding, internalization and degradation, receptor recycling, endosomal acidification, and receptor hyperphosphorylation, were investigated in both isolated hepatocytes and isolated perfused rat liver (1–3, 5, 12–17). In the current study we administered the labeled ligand and allowed endocytosis to proceed in vivo , and then processed the whole liver to isolate endosomes.…”
Section: Resultsmentioning
confidence: 85%
“…For the receptor, it seems that the receptor-containing endosomes are not being properly recycled and/or are being transported farther into the cell than that observed under normal conditions. Based on previous work in our laboratory, we knew that exposure of rats to ethanol resulted in impaired receptor-ligand dissociation (2,12,13); further, we observed impaired endosomal acidification in ethanol-fed rats compared with the controls using a fluid-phase marker, FITC-Dextran (4). In order to determine if the ethanol-induced shift in ligand and ASGP-R distribution between the two different endosome populations resulted from impaired receptorligand dissociation, we assessed the B/F ligand ratios in the endosome fractions.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol administration impairs hepatic protein metabolism at several steps along the protein transport pathway, including the cellular process of RME. We have extensively studied the process of RME by the hepatocyte-specific asialoglycoprotein receptor (ASGP-R) and have identified multiple steps of this pathway that are affected by ethanol treatment (Casey et al, 1987(Casey et al, , 1990Tworek et al, 1996Tworek et al, , 1997Tworek et al, , 1998b. The ASGP-R is an abundant endocytic receptor that is predominantly expressed on the sinusoidal surface of hepatocytes and has been well studied both in isolated hepatocytes and cultured liver cells of both human and rat origin.…”
Section: Carol a Caseymentioning
confidence: 99%